Opini Publik dan Politik Luar Negeri: Sikap Masyarakat Indonesia terhadap ODA Jepang dalam Proyek PLTA Koto Panjang dan Hubungan Bilateral Indonesia-Jepang - Keigo Kashiwabara (Universitas Diponegoro, 2016)
Japan has been playing an important role in the international society, especially in the field of the development of developing countries, through its ODA (Official Development Assistance). Indonesia, which has the biggest economic potential in Southeast Asia, is the largest recipient of Japanese ODA. Economic cooperation through ODA now functions as the core of the amicable bilateral relations between the two countries. However, ODA alternatively has had some negative aspects on its recipients. Some of the ODA projects (called Mondai-ankens) have actually triggered various problems at project sites and have consequently afflicted the local people. The most well-known mondai-anken that aroused national discussion on ODA policy is Koto Panjang Hydropower Plant Project implemented in Riau Province, in 1991-1997. The local community has been critical of Japanese ODA since the implementation of the project, which was done in a coercive manner under the Soeharto administration, caused costly damage to the local people such as poverty, scarcity of food, environmental destructuion, and so on. Although the mondai-anken issue caused considerable damage to the recipient country’s people, and the local commnity filed a complaint to the donor country, this issue had no political impact to the bilateral relations between the two countries.Keywords: ODA (Official Depelopment Assistance), Mondai-anken, Economic cooperation, Japan, Indonesia